2019
DOI: 10.1007/s11666-019-00951-4
|View full text |Cite
|
Sign up to set email alerts
|

Investigation of CMAS Resistance of Sacrificial Suspension Sprayed Alumina Topcoats on EB-PVD 7YSZ Layers

Abstract: Molten calcium-magnesium-aluminum-silicate (CMAS) mineral particles cause significant degradation of thermal barrier coatings (TBCs) in aero-engines. One approach to protect the TBC coating against the CMAS attack is the application of a sacrificial coating on top of the TBC coating. In this work sacrificial Al 2 O 3 coatings were deposited on top of EB-PVD 7YSZ layers using suspension thermal spraying starting from an aqueous Al 2 O 3 suspension. Spray parameters were varied in order to produce sacrificial to… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
8
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 10 publications
(10 citation statements)
references
References 22 publications
2
8
0
Order By: Relevance
“…Note that the depth R(T h ) of the CMAS-rich layer follows the parabolic law by Wu et al [25]. This study [24] also indicated that the infiltration behavior is initially faster and becomes slower as the holding time still operates.…”
Section: Resultssupporting
confidence: 67%
See 1 more Smart Citation
“…Note that the depth R(T h ) of the CMAS-rich layer follows the parabolic law by Wu et al [25]. This study [24] also indicated that the infiltration behavior is initially faster and becomes slower as the holding time still operates.…”
Section: Resultssupporting
confidence: 67%
“…The solid dots with bars and lines indicate the experimental data and the curve-fitting line. Based on previous studies [24], the depth ( ) h R T of the CMAS-rich layer can be defined by the parabolic law as follows:…”
Section: Resultsmentioning
confidence: 99%
“…The use of sacrificial coatings have also been explored, utilising Al 2 O 3 based top coats deposited by suspension plasma spray or suspension high velocity oxy-fuel spraying, on top of existing EB-PVD 7YSZ coatings [134]. The approach is interesting in that the Al 2 O 3 coating yields spinel layers that appear protective.…”
Section: Evaluation Of Cmas Mitigation Strategiesmentioning
confidence: 99%
“…GZO, Al2O3, 65YZ, etc. (19,(24)(25)(26)(27)(28)(29)(30).The principle of sacrificial layers is to form quickly a protective reaction layer during CMAS infiltration which consists of new crystalline phases with higher melting points. This layer inhibits further CMAS infiltration into the TBC.…”
Section: Introductionmentioning
confidence: 99%
“…This layer inhibits further CMAS infiltration into the TBC. These high-temperature stable phases, such as apatite, fluorite, garnet, zirconium, and especially spinel (in case of an Al2O3 sacrificial layer (31)), block the infiltration paths of the CMAS and serve as a barrier against further CMAS infiltration. Therefore, the further infiltration of CMAS into the underlying unreacted coating is inhibited.…”
Section: Introductionmentioning
confidence: 99%